Role of IGF2 in the Study of Development and Evolution of Prostate Cancer - Porras-Quesada, P.; González-Cabezuelo, JM.; Sánchez-Conde, V.; Puche-Sanz, I.; Arenas-Rodríguez, V.; García-López, C.; Flores-Martín, JF.; Molina-Hernández, JM.; Álvarez-Cubero, MJ.; Martínez-González, LJ.; Vázquez-Alonso, F. (Frontiers in Genetics, 2022)
Prostate Cancer (PC) is commonly known as one of the most frequent tumors among males. A significant problem of this tumor is that in early stages most of the cases course as indolent forms, so an active surveillance will anticipate the appearance of aggressive stages. One of the main strategies in medical and biomedical research is to find non-invasive biomarkers for improving monitoring and performing a more precise follow-up of diseases like PC. Here we report the relevant role of IGF2 and miR-93-5p as non-invasive biomarker for PC. This event could improve current medical strategies in PC.